OPTIMIZING IRRIGATION WATER BY DETECTING ACTIVE ROOT DEPTH USING NUCLEAR TECHNIQUE - A. Gomaa; M Hegazi; Kh. El-Bagoury; Kh. Youssef (Arab Universities Journal of Agricultural Sciences, 2018)
The experiment was carried out at the farm of soils and water research department, atomic energy authority. Inshas (latitude 30°24¢ longitude 31°35¢) altitude is 20 m above the sea level, during (2015/2016) growth season. The treatments of the water (T1,T2,T3), were applied, which was (100%, 80% and 60%), respectively based an estimated amount of applied water to active root depth (ARD) which estimated according to the amount of water depleted from field capacity through ARD. Actual evapotranspiration, yield, crop water use efficiency and active root depth were measured and estimated. The obtained results showed that the highest value of chickpea grain yield was 1218.09 kg/ha under T2  treatment compared with  1170.37 kg/ha and 919.99 kg/ha for (T1, T3) respectively. Also the highest value of crop water use efficiency was btained by T2 which was 0.28 kg/m3 flowed by T3 then T1 which were 0.26 and 0.22 kg m-3 respectively. Difference between the T1,T2 and T3 was found with grain yield and actual evapotranspiration between three treatments. Active root depth reached a maximum value was 71 cm, which approximates the actual value.